2016
DOI: 10.20853/30-4-570
|View full text |Cite
|
Sign up to set email alerts
|

Academic success, language and the four year degree: A case study of a 2007 cohort

Abstract: Tension exists between broadening access to tertiary education and ensuring throughput; as simply enrolling underprepared students into three-year degree programmes can be counterproductive, leading to failure and an increased dropout rate. Thus, correct placement of students and effective teaching interventions are crucial. On this basis, the University of Johannesburg implemented a four year BSc degree. Typical of many extended degree interventions, the first year was offered over a two year period, with an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…We need resources so that we don't have to wish to send our children to formerly White-only schools'. The under-preparedness of learners from poorly resourced public schools -the majority of whom are Black, given racialised apartheid-era schooling and socio-economic disparities -for higher education is well-documented (e.g., Mavunga, 2014;McKay, 2016). Evidently, South Africa's long-standing structural inequalities continue to disadvantage particularly Black students from low socio-economic backgrounds at various stages of their academic careers.…”
mentioning
confidence: 99%
“…We need resources so that we don't have to wish to send our children to formerly White-only schools'. The under-preparedness of learners from poorly resourced public schools -the majority of whom are Black, given racialised apartheid-era schooling and socio-economic disparities -for higher education is well-documented (e.g., Mavunga, 2014;McKay, 2016). Evidently, South Africa's long-standing structural inequalities continue to disadvantage particularly Black students from low socio-economic backgrounds at various stages of their academic careers.…”
mentioning
confidence: 99%
“…Van der Merwe (2018), comparing the acquisition of core academic language skills of a cross section of teacher education students, concluded that support in Year 1 only had limited effects. And, in an extended degree programme, McKay (2016), who used a structured academic literacy module in the first year, showed that although the most disadvantaged students did benefit from the intervention, this did not translate into academic success in the long term. In that study, almost 42% of the students were either academically excluded or switched qualifications.…”
Section: Review Of the Literaturementioning
confidence: 99%